2016
DOI: 10.1371/journal.pbio.1002440
|View full text |Cite
|
Sign up to set email alerts
|

Kif13b Regulates PNS and CNS Myelination through the Dlg1 Scaffold

Abstract: Microtubule-based kinesin motors have many cellular functions, including the transport of a variety of cargos. However, unconventional roles have recently emerged, and kinesins have also been reported to act as scaffolding proteins and signaling molecules. In this work, we further extend the notion of unconventional functions for kinesin motor proteins, and we propose that Kif13b kinesin acts as a signaling molecule regulating peripheral nervous system (PNS) and central nervous system (CNS) myelination. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 64 publications
0
28
2
Order By: Relevance
“…Although defects in ciliary TZ integrity and Shh signalling are hallmarks of many ciliopathies (see above), so far no disease-causing mutations have been identified in KIF13B. However, a recent study using mutant mice in which Kif13b was specifically ablated in Schwann cells or oligodendrocytes revealed a requirement for Kif13b in peripheral and central nervous system myelination 55 —processes known to involve primary cilia-mediated Shh signalling 56 57 58 59 60 . It will therefore be of interest to investigate potential Shh signalling defects in the conditional Kif13b mutant mice 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Although defects in ciliary TZ integrity and Shh signalling are hallmarks of many ciliopathies (see above), so far no disease-causing mutations have been identified in KIF13B. However, a recent study using mutant mice in which Kif13b was specifically ablated in Schwann cells or oligodendrocytes revealed a requirement for Kif13b in peripheral and central nervous system myelination 55 —processes known to involve primary cilia-mediated Shh signalling 56 57 58 59 60 . It will therefore be of interest to investigate potential Shh signalling defects in the conditional Kif13b mutant mice 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Activated p38α in presynaptic VTA neurons phosphorylate GIRK Kir3.1 to decrease somatic excitability and exocytosis of dopamine, allowing for development of place aversion in a behavioral conditioning task (Ehrich et al, 2015). Anxiety-related behavioral phenotypes are not apparent in p38γ knockout mice (Pogozelski et al, 2009;Ittner et al, 2016;Noseda et al, 2016) and have not been addressed for in p38β or p38δ knockout mice (Beardmore et al, 2005;Sumara et al, 2009).…”
Section: Anxietymentioning
confidence: 99%
“…A recent study using conditional Kif13b knockout mice showed how KIF13B through its interaction with DLG1 affects myelination positively in the peripheral nervous system but negatively in the central nervous system . Furthermore, DLG1 was reported to mediate recruitment of KIF13B to LRP1‐containing vesicles, forming a DLG1‐KIF13B‐LRP1‐complex, which in turn recruited UTRN .…”
Section: Trafficking Of Membrane Proteins Into and Out Of The Primarymentioning
confidence: 99%
“…Other reported binding partners or cargoes of KIF13B include CENTA1 [301,302], a phosphatidylinositol 3,4,5-triphosphate (PIP3)-binding protein that functions as a GTPase activating protein (GAP) for ARF6 [303]; the endothelial cell RTK VEGFR2 [304] and neuronal TRPV1 channels [305]. A recent study using conditional Kif13b knockout mice showed how KIF13B through its interaction with DLG1 affects myelination positively in the peripheral nervous system but negatively in the central nervous system [306]. Furthermore, DLG1 was reported to mediate recruitment of KIF13B to LRP1-containing vesicles, forming a DLG1-KIF13B-LRP1-complex, which in turn recruited UTRN [307].…”
Section: Modulation Of Ciliary Membrane Protein Trafficking and Signamentioning
confidence: 99%